A Delayed Presentation of Perforated Diffuse Large B Cell Lymphoma of the Small Bowel Resulting in a Large Interloop Faecaloma. (5th May 2022) - Zishan, Muhammed A.; Raufian, Kasra
Abstract : Primary small bowel lymphomas are a rare entity but with significant morbidity and a low five-year overall survival even after surgery. Its diagnosis is often delayed due to the lack of clear specific signs, unfamiliarity amongst clinicians, and the lack of screening tools. This often results in patients presenting with tumour-associated complications such as perforation, obstruction, or gastrointestinal bleeding which warrant urgent surgical intervention. We present the case of a patient presenting with a perforated small bowel lymphoma resulting in a large interloop extraluminal faecaloma causing subacute small bowel obstruction. He proceeded to have an emergency open right hemicolectomy and extended small bowel resection to facilitate gross resection of tumour which in conjunction with adjuvant systemic chemotherapy is considered current best practice to manage such neoplasms. Early referral to specialist centres and raising awareness of this rare entity will allow earlier recognition and therefore a more planned approach to the management of such pathology with fewer post-operative complications.